Slow deformation measurement of biological samples with 3D interferometric microscope - Schmit, Joanna; Reed, Jason C (Photonics Letters of Poland, 2012)
The 3D interference microscope is used to measure the mechanical and structural properties of biological samples. In this paper the pulsation of the eye of the zebrafish embryo and the motion of the neuron is measured. The measurement is often performed on a microsphere placed on a biological sample. The microsphere reflects a strong signal, and by applying a magnetic field the sphere can induce a controlled and varying pressure on the object. The deformation of the object and the motion of the sphere provide information about different mechanical properties of the biological sample. This paper specifically concentrates on the measurement of nanometric deformation at frequencies below 10Hz. Full Text: PDF References http://www.bruker-axs.com/white_light_interferometric_profilometers.html [Direct link] J. Schmit, K. Creath, J.C. Wyant, "Surface Profilers, Multiple Wavelength, and White Light Interferometry" in Optical Shop Testing, 667-755 (ed. D. Malacara, John Wiley, Hoboken 2007). J. Reed, M. Frank, J.J. Troke, J. Schmit, S.Han, M.A. Teitell J.K. Gimzewski, Nanotechnol. 19, 235101 (2008). [CrossRef] References 1-9 within: J. Reed, S. Ramakrishnan, J.Schmit, J.K. Gimzewski, "Mechanical interferometry of nanoscale motion and mechanical properties of living zebrafish embryos", www.acsnano.org 3(8), 2090 (2009). J. Reed, S. Ramakrishnan, J. Schmit, J. K. Gimzewski, "Mechanical interferometry of nanoscale motion and mechanical properties of living zebrafish embryos", www.acsnano.org 3(8), 2090 (2009). J. Schmit, K. Creath, App. Opt. 34(19), 3610 (1995). [CrossRef] J. Schmit, P. Unruh, E. Novak, "Measurement of object deformation with optical profiler", US Patent 7283250 (2007)